Upaya Pencegahan Anemia pada Remaja Putri Melalui Pentingnya Konsumsi Tablet Zat Besi (Fe): Efforts to Prevent Anemia in Teenage Daughters Through the Importance of Iron Tablet Consumption (Fe) - Kalsum, Umi; Andi Lis Arming Gandini; Sutrisno; Emmy Putri Wahyuni (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Anemia is a health problem in society worldwide, especially among young women. Anemia in adolescents hurts decreased immunity, impaired physical growth, mental development, concentration, learning achievement, adolescent fitness, and productivity if prevention is not carried out early. This community service activity aims to increase young women's knowledge and awareness of the importance of taking iron (Fe) tablets. The targets in this activity were young women attending school, teachers, and principals at SMA Negeri 9, 12, and 13 Samarinda City, with 326 participants. The method used in community service consists of situation analysis, planning, preparation, and implementation. The evaluation results showed increased participants' knowledge after obtaining information/messages about the importance of consuming iron (Fe) tablets in preventing anemia in female adolescents, which was indicated by an increase in the mean value of 12.92. So, continuing education for young women about the importance of consuming iron (Fe) tablets to prevent anemia will have long- and short-term impacts.